PENINGKATAN KUALITAS BERMAIN DALAM CABANG OLAHRAGA FUTSAL - Ariel Limbong; Azi Faiz Ridlo; Tatang Iskandar (An-Nizam, 2022)
The purpose of this paper is to educate teenagers around Malacca 4 about the latest regulations and also provide education about how to play well in futsal. This paper is the result of KKN activities that have been carried out with a program to improve the quality of sports games. The background of this problem is the lack of education or understanding of teenagers around Malacca 4 about the rules and how to play well in futsal. The Community Service Program implemented here contains three activities, namely; (1) Webinar "Socialization of the Latest Futsal Rules", (2) Coaching Clinic on how to play well in futsal, (3) Mini Tournament Fun Futsal Malacca 4. The purpose of the first activity is to socialize the latest rules of futsal, the second is to educate how to play futsal, the third is to evaluate the participants after participating in the previous activity. The location of the KKN Program is located on Jl. Malacca 4 Gang 1, Ex. Malacca sari, district. Duren Sawit, East Jakarta. This Community Service Program starts from February 25 to March 15. The methods used in this KKN program are (1) Socialization, (2) Training and Evaluation. The impact of this Community Service Program on the surrounding youth in Malacca 4 is that they understand more about the rules of futsal so that they can play more fairly even though there is no referee, increase sportsmanship in playing, and improve basic techniques in playing futsal.